Institutional complementarity for social and economic development - Yuriy Bilan; Tetyana Vasilyeva; Serhiy Lyeonov; Kseniya Bagmet (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
Today the prevention of global challenges (from global security to the problems of poverty) relates to the institutional quality. Nowadays, the social standards or other "social rules" make the part of the market system, since they are built into the country's institutional structure. Neither social nor economic reforms can be implemented without the support through institutional mechanisms. The purpose of this paper is to explore the relationship between social sector institutions and basic institutions, taking into account the economic development of countries and the way in which they are formed. A number of empiric studies confirmed significant role of institutions to provide conditions for economic development. In order to define and assess the link between the basic institutions and the social sector institutions, we formed panel data that includes 20 countries for the period from 2007-2014. We assessed quality of the basic institutions using The Worldwide Governance Indicators (WGI). WGI methodology provides an evaluation of six dimensions of the institutional quality that enables to define the connection and the impact of every dimension on the institutional quality of the social sector. The model additionally evaluates the impact of the incomes distribution inequality, general economic welfare on the institutional quality of the social sector. Among all dimensions of governance "Rule of Law" and "Regulatory Quality" the statistically significant direct impact on the institutional quality of the social sector has been revealed. It confirms the complementarity of basic institutions and institutions of the social sector.
Keywords: D02; I31; O17; 650; institutions; economic development; complementarity; institutional quality; social sector; dimensions of governance